Pelaksanaan Pembinaan Terhadap Narapidana dengan Perilaku Seksual Menyimpang di Lapas Perempuan Kelas IIA Pekanbaru Dikaitkan dengan Kepastian Hukum - Alfikri, Muhammad; Sabri, Fadillah; Mulyati, Nani (UNES Law Review, 2023)
Sexual deviance can be interpreted as everything related to sexual deviance, both in terms of orientation, interest, and surveillance to determine sexual attitudes. By not fulfilling the biological needs of female convicts, a lot of deviant sexual behavior occurs in the Class IIA Pekanbaru Women's Penitentiary. In order to fulfill their biological needs, prisoners are no longer ashamed to do things that are not common in prison. So it is necessary to make efforts to prevent deviant behavior in prisons. The formulation of the problem in this study is: 1. How is the implementation of coaching for convicts with deviant sexual behavior at the Class IIA Pekanbaru Women's Prison related to legal certainty? 2. What are the factors that cause deviant sexual behavior in Class IIA Women's Prison Pekanbaru? 3. What are the obstacles in fostering convicts with deviant sexual behavior at the Class IIA Pekanbaru women's prison? This research is a legal research that is descriptive in nature with an empirical juridical approach. The data used are primary data and secondary data. Data were collected through interviews, observation, and literature studies to then be processed and analyzed descriptively. From the results of the research and discussion, the results show that: 1. The development program is religious development, personality development and independence development are coaching programs that prioritize primary prevention strategy models. 2. Factors of same-sex relations in Class IIA Pekanbaru Women's Prison; Weak knowledge of religion, because of consensual feelings, because of the trauma of being hurt by men, because of environmental factors, abnormal sexual orientation naturally. 3. Obstacles in coaching are; There are no regulations governing, a lack of human resources for prison officers, a lack of interest in prisoners in the coaching process, a lack of facilities and infrastructure for Class IIA Pekanbaru Women's Prison.